(3ehLR JGQjN GdCacGQ GdEbJUGOjI YHQ GdYUhQ (B/s - (3CHh GdbeUGf, NGdOs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2001)
(3GdCacGQ GdEbJUGOjI aj GdaJQI eG bHd GdEbJUGO GdQCSeGdj(B- (3GdGacGQ GdEbJUGOjI aj GdaJQI GdQCSeGdjI(B- (3GdfXQjI GdcdGSjcjI(B- (3Cge GdeacQjf aj GdfXQjI GdfjhcdGSjcjI(B.s
Keywords: (3GdEbJUGOs; (3GdacQ GdEbJUGOjs